2021
DOI: 10.3389/fcell.2021.600506
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Clinicopathological Characterization of a Prognostic Immune Gene Signature Associated With MGMT Methylation in Glioblastoma

Abstract: Background: O6-methylguanine-DNA methyltransferase (MGMT) methylation status affects tumor chemo-resistance and the prognosis of glioblastoma (GBM) patients. We aimed to investigate the role of MGMT methylation in the regulation of GBM immunophenotype and discover an effective biomarker to improve prognosis prediction of GBM patients.Methods: A total of 769 GBM patients with clinical information from five independent cohorts were enrolled in the present study. Samples from the Cancer Genome Atlas (TCGA) datase… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…Additionally, although higher TAF12 expression was observed in patients older than 40 years in the CGGA and TCGA, this difference was not confirmed in the GEO datasets ( Supplementary Figure S1A ). Moreover, although previous studies reported that MGMT methylation was associated with a better prognosis and better response to chemotherapy in GBM patients [ 23 ], lower TAF12 expression was observed in samples with MGMT methylation in the CGGA ( Supplementary Figure S1B ). Furthermore, because of an update to the classification system, we also evaluated the expression level of TAF12 according to the grading of adult diffuse gliomas in the 2021 5th edition of the WHO classification of tumors of the CNS.…”
Section: Resultsmentioning
confidence: 81%
“…Additionally, although higher TAF12 expression was observed in patients older than 40 years in the CGGA and TCGA, this difference was not confirmed in the GEO datasets ( Supplementary Figure S1A ). Moreover, although previous studies reported that MGMT methylation was associated with a better prognosis and better response to chemotherapy in GBM patients [ 23 ], lower TAF12 expression was observed in samples with MGMT methylation in the CGGA ( Supplementary Figure S1B ). Furthermore, because of an update to the classification system, we also evaluated the expression level of TAF12 according to the grading of adult diffuse gliomas in the 2021 5th edition of the WHO classification of tumors of the CNS.…”
Section: Resultsmentioning
confidence: 81%
“…It should be pointed out that, while several reports have documented a correlation between IDH status and tumor infiltrating lymphocytes [17,49], the literature is scant about the identification of specific immunophenotypic characteristics associated with MGMT status and so far inconsistent results have been described [50,51]. On a large-scale RNAseq profiling of 769 GBM patients from five independent datasets, the score evaluation, defined as GBM-associated TIME immune cell infiltration (GTMEI) score, of more than 20 immune cell marker genes, including Thy-1 CD4, were analyzed in patients with different MGMT methylation status to define prognostic classes [52] and/or response to treatment [53]. While immune gene signatures were able to discriminate high-vs low-risk groups and to predict the response to chemo-or immuno-therapy, no differences were observed in the GTMEI score according to MGMT methylation status.…”
Section: Discussionmentioning
confidence: 99%
“…Dysfunction of tumor suppressor p53 is widely known to protect tumor cells from apoptosis, and accelerating evidence reveals that dysfunction also leads to inflammatory states and tumor-immune evasion [ 48 ]. However, the critical clinical biomarker MGMT is associated with an increased immune response [ 44 ], as analyses revealed an upregulation of immune genes in unmethylated glioma. Furthermore, there are further indications that inflammatory pathways influence the molecular properties and can represent biomarkers accordingly.…”
Section: The Tme Immune-state Is Receptive To the Molecular Heterogen...mentioning
confidence: 99%